2017
DOI: 10.1002/adsc.201700904
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Direct Trifluoro‐ and Perfluoroalkylselenolations of Boronic Acids with a Shelf‐Stable Family of Reagents

Abstract: Herein the copper‐catalyzed direct perfluoroalkylselenolation of aryl‐ and vinylboronic acids is described for the first time. The key to success is the design of new shelf‐stable perfluoroalkylselenolating reagents, namely perfluoroalkyl tolueneselenosulfonates. The reaction occurs at room temperature in the presence of commercially available catalyst and ligand in catalytic quantities.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 82 publications
2
44
0
3
Order By: Relevance
“…One major reactivity question remained:d oes the selenium derivative behave more like sulfur or tellurium (i.e.with Se in the + 4o r+ 6o xidation state in the final product)?A small number of aryl(trifluoromethyl)selanes were synthesized and subjected to TCICA/KF conditions ( Table 2). [15][16][17][18] As Yagupolskiisr esults with XeF 2 /HF suggest, [6] we found that the selanes undergo difluorination similar to sulfanes. Thus,c ompounds 21-26 were formed in good yields.T he 19 FNMR data of 15,for instance,can be compared to those of 25:in15,signals at d = À11.89 ppm (2F,q, 3 J F-F = 18 Hz) and d = À61.74 ppm (3F,t, 3 J F-F = 18 Hz) are observed, and in 25, the corresponding signals appear at d = À73.21 ppm (2F,q , 3 J F-F = 12 Hz) and d = À58.30 ppm (3F,t, 3 J F-F = 12 Hz).…”
Section: Angewandte Chemiesupporting
confidence: 64%
See 1 more Smart Citation
“…One major reactivity question remained:d oes the selenium derivative behave more like sulfur or tellurium (i.e.with Se in the + 4o r+ 6o xidation state in the final product)?A small number of aryl(trifluoromethyl)selanes were synthesized and subjected to TCICA/KF conditions ( Table 2). [15][16][17][18] As Yagupolskiisr esults with XeF 2 /HF suggest, [6] we found that the selanes undergo difluorination similar to sulfanes. Thus,c ompounds 21-26 were formed in good yields.T he 19 FNMR data of 15,for instance,can be compared to those of 25:in15,signals at d = À11.89 ppm (2F,q, 3 J F-F = 18 Hz) and d = À61.74 ppm (3F,t, 3 J F-F = 18 Hz) are observed, and in 25, the corresponding signals appear at d = À73.21 ppm (2F,q , 3 J F-F = 12 Hz) and d = À58.30 ppm (3F,t, 3 J F-F = 12 Hz).…”
Section: Angewandte Chemiesupporting
confidence: 64%
“…with Se in the +4 or +6 oxidation state in the final product)? A small number of aryl(trifluoromethyl)selanes were synthesized and subjected to TCICA/KF conditions (Table ) . As Yagupol'skii's results with XeF 2 /HF suggest, we found that the selanes undergo difluorination similar to sulfanes.…”
Section: Figurementioning
confidence: 72%
“…Trifluoromethyl tolueneselenosulfonate has been successfully evaluated in cross-couplingp rocesses with aryl boronic acids under copperc atalysis conditions (Scheme 29). [40] The developed methodology demonstrated ab road compatibility with different aryl boronic acid starting materials, substituted with electron-withdrawing or -donating groups. The reaction was performed with copper(II) acetate (10 mol %) in conjunction with bpy (10 mol %) as al igand, cesium carbonate as a base in THF at room temperature.…”
Section: Càsecf 3 Bond Formation Using An Electrophilic Secf 3 Reagentmentioning
confidence: 99%
“…Trifluoromethyl tolueneselenosulfonate has been successfully evaluated in cross‐coupling processes with aryl boronic acids under copper catalysis conditions (Scheme ) . The developed methodology demonstrated a broad compatibility with different aryl boronic acid starting materials, substituted with electron‐withdrawing or ‐donating groups.…”
Section: Direct Trifluoromethylselenolation Reactionsmentioning
confidence: 99%
“…[4,7] We designed recently an ew family of shelfstable reagents, namely perfluoroalkyl tolueneselenosulfonate. [8] With our continuous interest to develop new methodologies fort he incorporation of fluorinated moieties, we decided to investigate the direct formation of C(sp)ÀSeCF 3 through the direct coupling of alkynesw ith trifluoromethyl tolueneselenosulfonate under copperc atalysis. Regardingt he state of the art for the formation of C(sp)ÀSeCF 3 ,o nly few reports have been disclosed.…”
mentioning
confidence: 99%